2017
DOI: 10.1158/1078-0432.ccr-17-0743
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Breast Ductal Carcinoma In Situ Immune Microenvironment with Clinicopathological and Genetic Features

Abstract: Purpose: The immune microenvironment of breast ductal carcinoma in situ (DCIS) has yet to be fully explored, and the relationship of immune cells to genetic features of DCIS is unknown.Experimental Design: We quantified tumor associated lymphocytes (TIL) and evaluated PD-L1 protein levels by immunohistochemistry in a cohort of pure DCIS (138 and 79 cases, respectively), some of which had copy number (n ¼ 55) and mutation data (n ¼ 20).Results: TILs were identified in the stroma surrounding DCIS (119/138, 86%) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 44 publications
8
78
0
Order By: Relevance
“…Importantly, PD-1 þ or PD-L1 þ breast cancers with low XRCC1 were linked to aggressive cancers and reduced survival including in ERbreast cancers (13). As immune microenvironment (including PD-L1 þ TILs infiltration) in DCIS can influence aggressive phenotypes (28,29), we propose that PARP1 targeting may be a promising personalized approach either alone or in combination with immune checkpoint inhibitors in XRCC1deficient invasive cancers and in preinvasive DCIS.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, PD-1 þ or PD-L1 þ breast cancers with low XRCC1 were linked to aggressive cancers and reduced survival including in ERbreast cancers (13). As immune microenvironment (including PD-L1 þ TILs infiltration) in DCIS can influence aggressive phenotypes (28,29), we propose that PARP1 targeting may be a promising personalized approach either alone or in combination with immune checkpoint inhibitors in XRCC1deficient invasive cancers and in preinvasive DCIS.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have demonstrated that different pathological breast cancer subtypes have different genetic characteristics. TP53 and PIK3CA mutations are common in ductal breast carcinoma (18,19), while mucinous carcinoma lacks PIK3CA mutation (20). ERBB2 mutation is commonly present in both infiltrating lobular carcinoma and mucinous carcinoma (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that actin cytoskeleton signaling is associated with NG2 [29] and PDGFR [30], while integrin signaling is associated with S100A4 [31][32][33] and NG2 [34][35][36]. It has also been reported that molecular features that induce disease progression are different in each intrinsic molecular subtype of DCIS [24] and have an important role in the tumor microenvironment and progression of DCIS [37,38]. CAF-related proteins also have an intrinsic function.…”
Section: Discussionmentioning
confidence: 99%